2015
DOI: 10.1002/j.0022-0337.2015.79.12.tb06043.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Dental Students’ Self‐Directed, Faculty, and Software‐Based Assessments of Dental Anatomy Wax‐Ups: A Retrospective Study

Abstract: Little is known about self-directed and self-relective assessment in preclinical dental curricula. The aim of this study was to evaluate a visual dental anatomy teaching tool to train dental students to self-assess their dental anatomy wax carving practical examinations. The students self-assessed two waxing practical examinations (tooth #8 and tooth #19) using high-quality digital images in an assessment tool incorporated into a digital testing program. Student self-assessments were compared to the faculty ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 17 publications
(12 reference statements)
2
26
0
1
Order By: Relevance
“…Utilizing consistent techniques, Callan et al's study found that a user of CAD/CAM software could achieve a high degree of precision when evaluating preparations 1 . Other studies have found CAD/CAM software to be comparable to 14 or even more precise than 15 , 16 than faculty hand‐grading. In Hamil et al's study, dental students and faculty members showed overall positive attitudes toward the use of CAD/CAM software as a tool for objective evaluation and scoring 17 .…”
mentioning
confidence: 99%
“…Utilizing consistent techniques, Callan et al's study found that a user of CAD/CAM software could achieve a high degree of precision when evaluating preparations 1 . Other studies have found CAD/CAM software to be comparable to 14 or even more precise than 15 , 16 than faculty hand‐grading. In Hamil et al's study, dental students and faculty members showed overall positive attitudes toward the use of CAD/CAM software as a tool for objective evaluation and scoring 17 .…”
mentioning
confidence: 99%
“…This systematic process resulted in 24 articles being selected for inclusion in the review, seven had a low risk of bias [ 10 , 14 , 15 , 21 , 22 , 24 , 27 ], six had a high risk of bias [ 12 , 16 , 20 , 29 , 30 , 32 ], and eleven had an unclear risk of bias [ 13 , 17 19 , 23 , 25 , 26 , 28 , 31 , 33 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Computerized dental simulator (CDS) and virtual self-assessment (VSA) can offer a potential alternative feedback and assessment tools, which can enhance student's learning and self-assessment experiences [ 10 , 24 ]. CDS methods can provide a valuable perspective that is not offered by conventional assessments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations